Control of Computer and Electric Devices by Voice - Rudžionis, A.; Ratkevičius, K.; Dumbliauskas, T.; Rudžionis, V. (Elektronika ir Elektrotechnika, 2008)
Paper deals with the speech recognition software for controlling computer programs and electric devices by voice. Internet Explorer or any other computer program, which supports special keyboard combinations could be controlled by voice commands. The essential features of the control program are: the possibility to work with any installed in the system speech recognition engine, the possibility to make and to change voice commands and to change reactions to voice commands, the possibility to input the text by spelling. Electric devices could be turned on or turned off by voice with additional USB-based hardware. Speaker dependent projection based recognition algorithm, which was used in Lithuanian speech recognition engine, is described. The accuracy of recognition of ten Lithuanian commands by Lithuanian and English speech recognition engines was checked. Demonstrations of computer and electric devices control by voice commands are prepared. Ill. 4, bibl. 14 (in English; summaries in English, Russian and Lithuanian).